The role of Information Communication Technologies (ICTs) in Zimbabwean migrants’ experiences of maintaining care of transnational family. - Moyo, Siko Martin (My University, 2022)
The migration of Zimbabweans to South Africa is a common phenomenon. Migration is for various reasons, but socio-economic reasons are more common. Individuals migrate based on the need to take care of their families, something that they fail to do if they remained in Zimbabwe. Transnational families are created as a result. Very few studies have looked into how transnational relationships continue to exist over a long distance in the sub-Saharan African context. Furthermore, the role Information Communication Technologies (ICT’s) play in facilitating various forms of care such as emotional, moral, and financial has not been explored. The study consisted of nine Zimbabwean migrants residing in South Africa who had family that they cared for in Zimbabwe. The findings of this study reveal that ICT’s such as WhatsApp have been heavily adopted in these transnational families. This has been on account of convenience which the WhatsApp platform affords, such as being readily available, affordable, and comprehensive through calling, messaging and media share functions. These ICT’s have been found to assist people in remaining emotionally connected. ICT’s were used in rendering financial care, allowing migrants to pay for groceries and sending money. Other forms of care, such as medical care were found to be possible through use of these communication technologies. Lastly, the findings point out to ICT’s having disadvantages in the rendering of care as some care needs cannot be fulfilled online such as witnessing children grow or doing simple things like hugging loved ones. Other barriers for care using ICT’s involved high cost of ICT’s, and underdeveloped infrastructure which negatively impacted care relations. The need for physical contact, through visits, was confirmed as an additional disadvantage which ICT’s presented for transnational family care.
A research paper submitted in partial fulfilment for the degree of Master of Arts in Community Based Counselling Psychology in the Faculty of Humanities, University of the Witwatersrand, 2022